Study of the performance of ventilated sills for increasing the natural ventilation of schools in Maceió, Alagoas - Bittencourt, Leonardo Salazar (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The 2001 energy crisis in Brazil has pointed out the high energy waste that exists in this country. The need for increasing energy efficiency has intensified the discussion on the energy waste in buildings. As a consequence, the demand for highly energy efficient buildings has increased. These buildings should rely on the use of passive means for cooling and day-lighting, which decrease the demand for air-conditioning and artificial lighting systems. In order to take advantage of regional conditions, adapting buildings to the climate, the performance of some building components, such as the ventilated window-sill, needs further investigation. This paper examines the use of ventilated sills as a means for improving natural ventilation in classrooms. The quantitative and qualitative performance of this component in relation to natural ventilation has been assessed. The results indicate that the ventilated sill is able to increase the airflow inside the classrooms, especially at the work level of the students.